(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Recently, the main problem in the operation of hydraulic excavators is the contamination of hydraulic fluids with various minute dust impurities of rocks. As a result, there is a rapid wear of the parts of such machines. The article is devoted to the clarification of the composition of contaminated impurities. Microscopic analysis was used to study the clogging of hydraulic oil. The viscosity of the studied samples after their distillation decreased in comparison with the initial ones.